Appropriate, flexible and competitive architectural education - Ahmad, Mohd. Hamdan; Syed Ariffin, Syed Ahmad Iskandar; Megat Abdullah, Aminatuzuhariah; Ossen, Dilshan Remaz; Omar, Zatul Rawiyah (UTM, 2004)
Architectural education embraces all aspects of sciences and arts. Liberalization of markets, globalization and advancement in technology demand high responsibility in professional standards. Architectural education has no option but to stay parallel to the needs of the society. Consequently, architectural education has to respond to these demands of global market and provide education of highest international standards. This changes required architecture schools to conform to different expectations within university settings. The struggle to reconcile the disparate demands has led the schools to seek professional accreditation for their respective curriculum. However, these accreditation standards mainly emphasize only on practice-related skills. Thus, architectural education in universities experience tension between educational demand and the professional demand. This report reviews the pedagogical changes in the current architectural curriculums to face these new challenges and thereby determine factors influencing the appropriate, f lexibility and competitiveness of architectural education in general. The analysis was based on the degree of core and elective subjects, degree conferred and the duration, and level of professional accreditation of the architectural education. The analysis of curriculums was carried out based on RIBA criteria for validation. The RIBA requirements were further evaluated using Blooms (1956) intellectual behaviors of learning outcome. The study was conducted on twelve selected universities from the Asian region, Australia, New Zealand, United Kingdom and America. The results showed that architectural education in universities are far beyond professionalism and demand for research based curriculums.